2014
DOI: 10.1186/1472-6963-14-117
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes patient management by pharmacists during Ramadan

Abstract: BackgroundMany Muslim diabetes patients choose to participate in Ramadan despite medical advice to the contrary. This study aims to describe Qatar pharmacists’ practice, knowledge, and attitudes towards guiding diabetes medication management during Ramadan.MethodsA cross-sectional descriptive study was performed among a convenience sample of 580 Qatar pharmacists. A web-based questionnaire was systematically developed following comprehensive literature review and structured according to 4 main domains: subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Most reported being willing to attend a workshop to learn about the adjustment of medication regimens during RamadanAmin and Chewning [20]Alexandria, EgyptCS; analyzed the responses from the above study to explore the utility of the planned behavior theory model in predicting the behavior of pharmacists towards adjusting medication regimens for patients during RamadanRandom sampling out of a list of 3309 community pharmacies in Alexandria277 pharmacists93%Sample pharmacists were more likely to change simpler aspects of patient medications (e.g., dose regimen changes, rather than recommending a different class of medications). In this sample, current practice was limited to minimal intervention delivery, which is perhaps reflective of provider confidenceWilbur et al [45]QatarCS descriptive study using a Web-based custom developed questionnaire that contains items focussed on pharmacist attitudes towards appropriate patient care and knowledge about medication adjustments for patients with diabetes who were undertaking the Ramadan fast. This was completed by participants 3 months prior to Ramadan 2012Convenience sample obtained from Qatar University College of Pharmacy—internal pharmacist database178 pharmacists31%Pharmacists reported frequent encounters with patients who have diabetes during Ramadan.…”
Section: Resultsmentioning
confidence: 99%
“…Most reported being willing to attend a workshop to learn about the adjustment of medication regimens during RamadanAmin and Chewning [20]Alexandria, EgyptCS; analyzed the responses from the above study to explore the utility of the planned behavior theory model in predicting the behavior of pharmacists towards adjusting medication regimens for patients during RamadanRandom sampling out of a list of 3309 community pharmacies in Alexandria277 pharmacists93%Sample pharmacists were more likely to change simpler aspects of patient medications (e.g., dose regimen changes, rather than recommending a different class of medications). In this sample, current practice was limited to minimal intervention delivery, which is perhaps reflective of provider confidenceWilbur et al [45]QatarCS descriptive study using a Web-based custom developed questionnaire that contains items focussed on pharmacist attitudes towards appropriate patient care and knowledge about medication adjustments for patients with diabetes who were undertaking the Ramadan fast. This was completed by participants 3 months prior to Ramadan 2012Convenience sample obtained from Qatar University College of Pharmacy—internal pharmacist database178 pharmacists31%Pharmacists reported frequent encounters with patients who have diabetes during Ramadan.…”
Section: Resultsmentioning
confidence: 99%
“…medication adjustment) prior to the month-long fast. (17) Structured education and interventional programmes, for both Muslim patients with DM and healthcare professionals involved in the care of these patients, (18)(19)(20)(21) are important to bridge the knowledge gap and to correct inappropriate practices so that the complication rates observed among these patients during Ramadan can be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Section 1 tested the patients' general knowledge of DM using a modified, 16-item version of the validated Michigan Diabetes Knowledge Test (MDKT). (9) All of the questions from the original MDKT were retained, except for Questions 4,15,17,18,19,21 and 23, and one option each in Questions 1 and 2 were modified to better suit the Singapore population (Appendix). The patients were required to select the best answer for each of the 16 multiple-choice questions.…”
Section: Knowledge Of Diabetes Mellitus and Safe Practices During Rammentioning
confidence: 99%
“…15 That said, research in other predominantly Muslim countries, such as Qatar and Pakistan, has shown that pharmacists and physicians with a good knowledge of Islam still have knowledge gaps about how to adjust medications safely. [16][17][18] In other words, there is plenty of opportunity to support Muslim patients during Ramadan, but we all have a lot to learn about how to do so safely.…”
Section: Role Of the Pharmacistmentioning
confidence: 99%